Determinants of Profitability in Nepalese Insurance Companies - Bhattarai, Saajan; Karki, Sabina; Pant, Sagar Nath; Bohara, Santosh (Nepalese Journal of Finance, 2024)
This study examines the determinants of profitability in Nepalese insurance companies. Return on assets (ROA) and return on equity (ROE) are the dependent variables. The selected independent variables are firm size, liquidity, tangibility, firm age, premium growth and total capital. The study is based on secondary data of 27 insurance companies with 108 observations for the study period from 2018/19 to 2021/22. The data were collected from the annual reports of selected Nepalese insurance companies. The regression models are estimated to test the significance and effect of firm specific factors on the profitability of Nepalese insurance companies. The study showed that liquidity ratio has a negative impact on return on assets and return on equity. It means that increase in liquidity ratio leads to decrease in return on assets and return on equity. In contrast, assets tangibility has a positive impact on return on assets and return on equity. It shows that higher the assets tangibility, higher would be the return on assets and return on equity. Similarly, firm age has a positive impact on return on assets and return on equity. It means that increase in firm age leads to increase in return on assets and return on equity. Furthermore, premium growth has a positive impact on return on equity. It means that higher the premium growth, higher would be the return on equity. In addition, total capital has the positive impact on return on assets. It indicates that higher the total capital, higher would be the return on assets and return on equity.